A government librarian's guide to information governance and data privacy - Elin, Phyllis; Rapaport, Max (Business Expert Press, 2022)
This book provides a concise and usable overview of the practical implications of important public sector United States federal, state, and municipal laws and standards related to information governance, as they pertain to librarians, research staff, universities, corporate regulatory managers, and public-sector information governance professionals. It is the first in a series of two volumes addressing public sector information governance compliance matters from the perspective of our target audience. Topics addressed in the book include: the evolving role of librarians and the need for librarians and legal researchers to understand the principles of information governance, the importance of broad-based regulatory IG principles such as the Federal Records Act, the Paperwork Reduction Act of 1980 and 36 CFR Chapter XII, Subchapter B - Records Management, that have been promulgated by various federal government agencies in framing public-sector IG principles, a survey of interpretive surveys from the Office of Management and Budget (OMB) that further elucidate the core IG principles applicable to public sector stakeholders, case studies detailing the application of important IG principles by federal agencies and bodies, and a survey of important IG issues facing state and local governments.